STUDI EMPIRIS THEORY OF PLANNED BEHAVIOR TERHADAP INTENSI MAHASISWA MENJADI AKUNTAN - Dhani Vyrdha Anggraita Putri (BAJ: Behavioral Accounting Journal, 2019)
This study aims to analyze Theory of Planned Behavior influencing students' intention to be accountants, where subjective norms, attitudes, and behavioral perceptions can be useful for understanding various behaviors that can influence their decisions. Besides, a state defense behavior also supports the behavior of accountants. This type of research is quantitative research with an approach from Theory of Planned Behavior that is related to the intention of students to become accountants. The type of data used is primary data, which collected by distributing questionnaires to the Postgraduate students of UPN "Veteran" East Java. The analysis technique used in this study is to use the PLS (Partial Least Square) approach. The results showed that the Theory of Planned Behavior proved to influence the intention of students to become accountants, thus it can be said that the UPN "Veteran" East Java graduate students have high confidence in being accountants and tend to have high intentions to become accountants.